ProProtein: A platform for fully automated identification of 3D structure fluctuations in MD simulation trajectories - Krzysztof Mularski; Dawid Makalowski; Marcin Okonek; Daria Glebowska; Mateusz Swiercz; Karol Kamel; Jacek Blazewicz; Maciej Antczak; Aleksandra Swiercz (PLoS ONE, 2025)
The main goal of Molecular Dynamics (MD) is a simulation of a physical system motions in a fixed time period. This technique allows users to observe the dynamic evolution of the system but requires advanced force fields and is computationally intensive. Furthermore, finding desirable features in the results obtained is usually a time-consuming task. This motivates the need to implement a tool that visualizes the most flexible protein fragments. ProProtein platform is a sophisticated web server where, with a single click, the user can set up, configure, and run an MD simulation of the 3D structure of the peptide/protein. We perform the simulation using an open-source software suite developed for high-performance molecular dynamics named Gromacs. The resulting MD trajectory is then automatically analyzed within the dedicated heuristic algorithm to identify 3D fragments characterized by high instability in the context of the given (input) structure. These high-fluctuation substructures are presented next to the user with the Mol* package. They are visualized in colors on each frame covered by the considered trajectory. This tool can easily support the evaluation of the reliability of protein 3D structure predictions obtained computationally. The ProProtein platform is free and open to all users. It is publicly available at: https://proprotein.cs.put.poznan.pl/.